2000
DOI: 10.1128/jb.182.24.7007-7013.2000
|View full text |Cite
|
Sign up to set email alerts
|

TheSaccharomyces cerevisiae ICL2Gene Encodes a Mitochondrial 2-Methylisocitrate Lyase Involved in Propionyl-Coenzyme A Metabolism

Abstract: The Saccharomyces cerevisiae ICL1 gene encodes isocitrate lyase, an essential enzyme for growth on ethanol and acetate. Previous studies have demonstrated that the highly homologous ICL2 gene (YPR006c) is transcribed during the growth of wild-type cells on ethanol. However, even when multiple copies are introduced, ICL2 cannot complement the growth defect of icl1 null mutants. It has therefore been suggested that ICL2 encodes a nonsense mRNA or nonfunctional protein. In the methylcitrate cycle of propionyl-coe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
96
0
7

Year Published

2001
2001
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(107 citation statements)
references
References 36 publications
3
96
0
7
Order By: Relevance
“…The enzyme is encoded by the ICL2 gene which is induced using threonine as a nitrogen source. Obviously, this amino acid is degraded via 2-oxobutyrate to propionylCoA followed by oxidation to pyruvate via the methylcitrate cycle [14]. Chemical and enzymatic syntheses of 2-methylisocitrate revealed that the substrate for both 2-methylisocitrate lyases is the same enantiomer of the threo-diastereomeric pair.…”
Section: Discussionmentioning
confidence: 99%
“…The enzyme is encoded by the ICL2 gene which is induced using threonine as a nitrogen source. Obviously, this amino acid is degraded via 2-oxobutyrate to propionylCoA followed by oxidation to pyruvate via the methylcitrate cycle [14]. Chemical and enzymatic syntheses of 2-methylisocitrate revealed that the substrate for both 2-methylisocitrate lyases is the same enantiomer of the threo-diastereomeric pair.…”
Section: Discussionmentioning
confidence: 99%
“…The S. cerevisiae genome does not encode a propionyl-CoA carboxylase and therefore cannot catabolize propionyl-CoA via the methylmalonyl-CoA pathway. However, there is evidence that propionylCoA is catabolized via the methylcitrate cycle in S. cerevisiae (69,70). No gene has been associated with the reported bacterial 2HG synthase activity yet, hampering the search for a 2HG synthase candidate gene in other genomes.…”
Section: Identification Of a New Type Of Enzymatic Activity For Degramentioning
confidence: 99%
“…The methylcitrate cycle is used for the assimilation of propionate via propionyl-CoA, which is generated from the oxidation of odd-chain fatty acids or amino acids, such as threonine or methionine (Luttik et al, 2000). The methylcitrate cycle genes are induced by propionate (Epstein et al, 2001a) and are not expressed under anaerobic conditions in a glucose-limited chemostat culture (Ter Linde et al, 1999).…”
Section: Genes Affected By Multiple Tca Cycle Defectsmentioning
confidence: 99%
“…The function and species distribution of the methylcitrate cycle are still poorly understood, but this pathway is intimately linked to the TCA cycle. The three distinct enzymes of this mitochondrial pathway: methylcitrate synthase, methylaconitate dehydratase, and methylisocitrate lyase, appear to be encoded by the CIT3, PDH1, and ICL2 genes, respectively (Luttik et al, 2000;Horswill and Escalante-Semerena, 2001). Expression of PDH1 was altered in 13 of the 15 mutant strains, and CIT3 and ICL2 were also highly responsive to TCA cycle defects.…”
Section: Genes Affected By Multiple Tca Cycle Defectsmentioning
confidence: 99%